1998
DOI: 10.1088/0953-4075/31/9/020
|View full text |Cite
|
Sign up to set email alerts
|

On the calculation of electron-impact rotational excitation cross sections for molecular ions

Abstract: Methods of computing rotational excitation cross sections for electron collisions with diatomic molecular ions are examined for impact energies up to 5 eV. The HeH + and NO + ions are used as test cases and calculations are performed at various levels of approximation. Previous studies have all used the Coulomb-Born approximation assuming only dipolar potentials. This approximation is found to be unreliable in a number of aspects: short-range and threshold effects are important, and the widely made assumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 26 publications
2
28
0
Order By: Relevance
“…(12). The required value of the cross section constant σ 0 (amounting to ∼10 4Å2 ) is not unrealistic [55] and slightly smaller values may in fact be sufficient if transitions other than ∆J = ±1 [54] are considered in addition. Fig.…”
Section: Rotational Excitation and Coolingmentioning
confidence: 98%
“…(12). The required value of the cross section constant σ 0 (amounting to ∼10 4Å2 ) is not unrealistic [55] and slightly smaller values may in fact be sufficient if transitions other than ∆J = ±1 [54] are considered in addition. Fig.…”
Section: Rotational Excitation and Coolingmentioning
confidence: 98%
“…If one considers the integral over the resonance region, however, these resonances do not change the probability significantly. Thus, as previously observed by Rabadán et al (1998) for diatomic ions, a detailed treatment of vibrational motion is unnecessary to obtain reliable thermally-averaged rotational excitation rate coefficients of the type normally needed in astrophysical applications. On the other hand, in the region between the (2, 1) and (3, 1) channels, Rydberg resonances are found to increase the rotational probability by about a factor of 2 on average, i.e., the value of 0.15 just above the (3, 1) channel increases discontinuously to an averaged value of 0.29.…”
Section: Mqdt-rft Methodsmentioning
confidence: 95%
“…The CB theory thus predicts that transitions with ∆J=1 and 2 only are allowed for dipole and quadrupole interactions, respectively. Recent ab initio R-matrix studies on several astronomically important molecular ions have shown, however, that this prediction is incorrect and that the inclusion of short-range interactions is crucial, particularly for ions with small (or zero) dipole or transitions with ∆J > 1 (see Rabadán et al (1998), Faure and Tennyson (2002b) and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…photo-electrons. Recent studies of rotational excitation include H2 (Danby et al 1996), HeH+ and N0+ (Rabadan et al 1998), CO (Randell et al 1996), 0 2 (Mukherjee & Ghosh 1996), H 2 0 (Gianturco et al 1998a), 0 3 (Gianturco et al 1998b), C 0 2 (Gianturco & Stoecklin 1997), and S 0 2 ). Vibrational excitation due to electron collisions has been investigated for H 2 (Lee et al 1996a;Kazanskii 1996;Mazevet et al 1998), HD (Kazanskii 1996), N 2 (Grimm-Bosbach et al 1996;Sweeney & Shyn 1997), OH (Chen & Morgan 1997), CO , and CH 4 (Bundschu et al 1997) while studies of electronic excitation of H 2 (Celiberto et al 1996), CO (Lee et al 1996b;Zubek et al 1997;Zetner et al 1998), CO, C0 2 , and S0 2 (Fomunung et al 1996), N 2 (Gillan et al 1996), NO (Mojarrabi et al 1996), 0 3 (Sweeney & Shyn 1996), H 2 0 (Morgan 1998), H 2 S (Michelin et al 1997), and CH4 and SiH4 (Bettega et al 1998) have been performed.…”
Section: Electron Impact Of Moleculesmentioning
confidence: 99%